Transformational Leadership And Lecturer Commitment To Organizational Change With The Moderation Effect Of Organizational Culture At The Faculty Of Tarbiyah State Islamic Institute Of Madura - Kusuma, Dwi Putera; Roesminingsih, Erny; Khamidi, Amrozi (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
The purpose of this study is to measure the influence of transformational leadership on organizational change, measure the influence of lecturer commitment to organizational change, and measure the influence of transformational leadership and lecturer commitment to organizational change with the moderation effect of organizational culture at the Faculty of Tarbiyah State Islamic Institute of Madura. This research uses a quantitative type of research design through associative causal survey research, namely asking about the relationship or influence between the independent/free variable (influence) and the dependent/bound variable (influenced). Research conducted by survey determines the value of several variables, from several hypotheses regarding the actions and characteristics of an object. Data collection was carried out using a questionnaire instrument given to all. Data analysis uses simple linear regression to test how influential transformational leadership is on organizational change, and multiple linear regression to test how influential transformational leadership and lecturer commitment together are on organizational change with the moderating effect of organizational culture at the Faculty of Tarbiyah State Islamic Institute of Madura. Based on the results of this data analysis, three research conclusions were obtained. First, the transformational leadership applied by leaders at the Faculty of Tarbiyah IAIN Madura has a very significant influence on organizational change. Second, lecturer commitment has a very significant influence on organizational change. Third, transformational leadership and lecturer commitment simultaneously or together have a very significant influence on organizational change with the moderating effect of organizational culture.